The trends of academic achievement among Malaysia boys and girl: where are the boys? - Ahmad, Nor Aniza; Hassan, Siti Aishah; Ahmad, Abdul Razak; Chua, Lay Nee; Othman, Nor Hashim (Global Academy of Training and Research, 2017)
Objective – Gender differences in education remain as one of the global issues that has been widely and comprehensively discussed. This study aims at exploring the pattern of academic achievement of boys and girls in Malaysia.